2000
DOI: 10.1016/s0378-1097(99)00599-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a cystathionine β/γ-lyase from Lactococcus lactis ssp. cremoris MG1363

Abstract: This paper describes the nucleotide sequence of a gene encoding cystathionine L/Q-lyase from Lactococcus lactis ssp. cremoris MG1363, its overexpression in Escherichia coli and some functional characteristics of the purified recombinant protein. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…Taking the results together, we concluded that MetC catalyzes both an ␣,␤-and an ␣,␥-elimination reaction. This property has also been reported for the CBL of L. lactis (1,15).…”
Section: Vol 74 2008 Two L Casei Genes Encoding a Cystathionine Lysupporting
confidence: 80%
“…Taking the results together, we concluded that MetC catalyzes both an ␣,␤-and an ␣,␥-elimination reaction. This property has also been reported for the CBL of L. lactis (1,15).…”
Section: Vol 74 2008 Two L Casei Genes Encoding a Cystathionine Lysupporting
confidence: 80%
“…Only low quantities of VSC were produced by LAB when cultivated alone. LAB and mainly L. lactis, the major species in our starter mixture, was found to possess two enzymes, cystathionine β-lyase and cystathionine γ -lyase, which were able to convert L-methionine to methanethiol [2,16]. However, these enzymes exhibit low specificity towards L-methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Two enzymatic pathways in lactococci have been postulated. In the first one, a single-step route, a lyase (cystathionine ␤-or ␥-lyase), catalyzes the simultaneous deamination and demethylthiolation of Met to MTL (2,10,14,17). In Brevibacterium linens, disruption of the mgl gene encoding L-methionine ␥-lyase, which catalyzes the ␣,␥-elimination of Met to MTL, almost eliminated this strain's considerable capacity to produce VSCs (3).…”
mentioning
confidence: 99%